Sports arbitration as a mechanism for upholding sports ethics in the light of resolving sports disputes - SAÂDA, Ben Ziane; SALEM, Mohamed (Art Law and Accounting Reporter, 2026)
Sports arbitration consistently operates beyond rigid legal rules, seeking instead to establish a balanced equation between conflicting interests while taking into account the specific nature of sport and the need to preserve the integrity of competitions. In doing so, arbitration contributes to the consolidation of sports ethics not only at the level of athletic performance but also in the contractual relations and commercial practices surrounding sporting activity.